2010
DOI: 10.1007/s10562-010-0389-x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Zirconia as an Efficient Catalyst for Sulfonylamidomethylation of Benzylsulfonamides and 2-Phenylethanesulfonamides: Effect of Catalyst Thermal Treatment

Abstract: The synthesis of 3,4-dihydro-1H-2,3-benzothiazine 2,2-dioxides and 1,2,4,5-tetrahydro-3,2-benzothiazepine 3,3-dioxides is studied using sulfated zirconia as catalyst. The sulfated zirconia calcined at 550°C achieved a high selectivity which is attributed to the formation of a tetragonal phase. In addition, the catalyst can be reused up to three times without loss of its catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
5
0
3
Order By: Relevance
“…1. It can be observed that all catalysts exhibited the characteristic peaks corresponding to a mixture of monoclinic and tetragonal zirconia phases [28,29]. In general, incorporation of the promoters stabilizes the tetragonal phase of zirconia [30].…”
Section: Catalyst Characterizationmentioning
confidence: 92%
See 1 more Smart Citation
“…1. It can be observed that all catalysts exhibited the characteristic peaks corresponding to a mixture of monoclinic and tetragonal zirconia phases [28,29]. In general, incorporation of the promoters stabilizes the tetragonal phase of zirconia [30].…”
Section: Catalyst Characterizationmentioning
confidence: 92%
“…Whereas in the case of promoted zirconia catalysts, lines due to tetragonal phase are more intense. Raman bands in the range of 1000-1150 cm À1 for the SZ catalyst are due to the presence of different surface sulfated groups [29,32]. Further, the MZ catalyst exhibits two additional bands at around 820 and 990 cm À1 corresponding to the formation of Zr (MoO 4 ) 2 compound between zirconia and molybdenum [33].…”
Section: Catalyst Characterizationmentioning
confidence: 93%
“…The patterns show reflections on the 2θ scale at 30.3°, 35.3°, 50.3° and 60° attributed to tetragonal phase corresponding to (101), (110), (112) and (211) planes (ICSD#085322) respectively. In addition to these reflections, small peaks at 2θ=28.34° and 31.4° attributed to monoclinic phase corresponding to (−111) and (111) planes (ICSD#068782) respectively ,. for zirconia (HC−Z) were also observed.…”
Section: Resultsmentioning
confidence: 99%
“…Otra aplicación de la catálisis heterogénea en la sulfonilamidometilación es la ciclización de las bencilsulfonamidas y 2-feniletilsulfonamidas a las correspondientes 3,4-dihidro-1H-2,3-benzotiazinas 2,2-dióxido y 1,2,4,5-tetrahidro-3,2-benzotiazepinas 3,3-dióxido empleando zirconia sulfatada como catalizador ácido heterogéneo. (43) En la ciclización de las bencilsulfonamidas los mejores resultados se obtuvieron para R 1 =m-Cl, R 2 =H; R 1 =H, R 2 =n-Bu; R 1 =H, R 2 =Et; con rendimientos superiores a 95 %. Los tiempos de reacción variaron de 3 a 24 h no reportándose la obtención de productos cinéticos de reacción.…”
Section: Esquema 22unclassified
“…Las N-sulfoniltetrahidroisoquinolinas (41) se obtuvieron con buen rendimiento en los casos en que el anillo estaba sustituido con grupos atractores de electrones mientras que la formación de los productos competitivos (42,43) solo fue importante en el caso donde R es un grupo donor de electrones (-OCH3) o cuando se empleó tricloruro de aluminio como catalizador.…”
Section: (Esquema 25)unclassified